2008
DOI: 10.1016/j.otohns.2007.11.016
|View full text |Cite
|
Sign up to set email alerts
|

Microdebrider vs electrocautery: A comparison of tonsillar wound healing histopathology in a canine model

Abstract: In a canine model of tonsillar wound healing, microdebrider intracapsular tonsillectomy produced significantly faster healing than electrocautery tonsillectomy in the early postoperative course. The "biologic dressing" theory of intracapsular tonsillectomy wound healing may account for observed differences in healing and suggests a mechanism for improved clinical outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
34
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(42 citation statements)
references
References 21 publications
1
34
0
Order By: Relevance
“…From then on, a plenty of findings have held up their opinions which indicate that MIT is superior to conventional surgical excision in some aspects including the amount of blood loss, dehydration, and postoperative recovery time [4][5][6]. Recent researches indicate that MIT is valid for protecting the tonsillar capsule and producing fast wound healing to reduce suffering [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…From then on, a plenty of findings have held up their opinions which indicate that MIT is superior to conventional surgical excision in some aspects including the amount of blood loss, dehydration, and postoperative recovery time [4][5][6]. Recent researches indicate that MIT is valid for protecting the tonsillar capsule and producing fast wound healing to reduce suffering [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…There were very few studies found in the literature concerning healing time of the tonsillar fossae [10][11][12]. Timms and Temple [10,13] compared coblation and BET and observed complete healing in the 9th postoperative day.…”
Section: Discussionmentioning
confidence: 99%
“…Timms and Temple [10,13] compared coblation and BET and observed complete healing in the 9th postoperative day. Johnson et al [11] compared microdebrider partial tonsillectomy with electrocautery and found that healing starts earlier in the microdebrider group. Stavroulaki et al [12] compared thermal welding with cold dissection and found no significant differences between them on the 10th postoperative day.…”
Section: Discussionmentioning
confidence: 99%
“…Surgeons have given acetaminophen (2), dexamethasone (3), gabapentin (4), fibrin glue (5), and fusafungine (6). Various surgical techniques have been described for better pain relief and wound healing, such as harmonic scalpel (7), cryotherapy (8), microdebrider (9), and laser coblation (10) .…”
Section: Introductionmentioning
confidence: 99%